Some SLiCA project results from Chukotka - Abryutina, Larisa (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractThis article is about the Chukotkan component of the international project “Survey of Living Conditions in the Arctic” (SLiCA). The research investigated various aspects of the lives of Aboriginal peoples in Chukotka and compared them with data from Aboriginal peoples of different countries. One of the advantages of the SLiCA project was that researchers worked with Aboriginal people as partners to design and implement the study. In this paper, statistical data obtained previous to SliCA and those collected during the SLiCA project are presented.